RELASI AGAMA DAN PILIHAN NASABAH: GROUNDED THEORY DAN REPOSISI AGAMA PADA PILIHAN NASABAH BANK SYARIAH DI BENGKULU - Hardivizon Hardivizon; Mhd. Sholihin; Anrial Anrial (Universitas Islam Negeri Imam Bonjol Padang, 2016)
This paper certainly examines the relationship between religion and consumer’s choice towards the islamicbank in Bengkulu, Province. Concerning in religion preference system and its relation with consumer’s choicethe research is crucially expected to discover the relationship between religion, and the consumer’s choice ofislamic bank in Bengkulu. The reason why the issues must be studied is from theoritical foundation in whichbelief system like religion, and rationality is a main factor determining the consumer’s choice towards islamicbank in varied-cases (Yusof; Bahari; Adanan: 2014). Hence, there are various facts as an important settingof research—moeslem population in Bengkulu; level of FDR (finance to deposits ration) for many islamicbank in Bengkulu is 182,3% and also NPF level is 3.30%. Based on this setting, the study intentionaly usesthe grounded theory as approach. It directly legitimates two theories as guidance for the research—rationalitychoice theory and shopping preference theory.The research successfully finds a set of thesis that religion’s rules in consumer’s choice of islamic bank can bedescribed shortly in two models—religion as Model of ” and “for Reality. These models emerge in consumer’sbehaviour of how they select the islamic bank in Bengkulu. Empirically, it can be attested from the perception,and definition toward islamic bank as a personal experience. In fact, Islam as a part of religions modifiedas justification for their choice. Whilst consumers tend to be a loyal consumer of Islamic bank based on thebelief– framework produced from their religion, for some users it is eventually because of the economics interest.For example, islamic bank choice is based on the ultimate-goal to gain exceeded-profit rather merits offeredby the conventinal bank.